Beyond Tourism: The Ways of Salatiga Culinary Business People to Survive Covid-19 - Setiawan, Rio Giovano; Lasso, Aldi Herindra (Lasigo Akademia Indonesia, 2024)
During the COVID-19 pandemic, the sustainability of tourism-related livelihoods was significantly impacted. Tourism-related SMEs, including culinary businesses, have strived to find ways to endure the pandemic. Therefore, developing strategies to cope with the crisis became essential. Viewing the COVID-19 pandemic in a holistic context, responses from culinary entrepreneurs indicate a context of the crisis that can either harm them as a vulnerable context or serve as an opportunity to improve their livelihoods. Within the framework of sustainable livelihood theory, this research examines the efforts of Salatiga culinary entrepreneurs in securing their livelihoods during the COVID-19 pandemic. Presenting an empirical case of culinary entrepreneurs in Salatiga, Central Java, Indonesia, this research employs a qualitative approach and collects data through in-depth interviews, observations, and document studies. The interviews were conducted during participants’ spare time, with repeated visits made to acquire detailed information. The results indicate that while major culinary entrepreneurs have managed to keep their businesses afloat, some have chosen to pivot to other industries. In conclusion, those entrepreneurs who diversified their businesses beyond the tourism sector have become more adaptable in adjusting their livelihoods to the pandemic and are better prepared for the unpredictable duration of the COVID-19.